Microsoft PowerPoint 2010 bible - Wempen, Faithe (Wiley Pub., 2010)
"Get the very most out of all that PowerPoint 2010 has to offer while also learning priceless tips and techniques for making good presentations in this new PowerPoint 2010 Bible. Well-known PowerPoint expert and author Faithe Wempen provides formatting tips; shows you how to work with drawings, tables, and SmartArt; introduces new collaboration tools; walks you through five special presentation labs; and more"--Resource description page.